The effect of an efficient public transport system on poverty: lessons for Johannesburg from Bogota - Mpofu, Eugenia (My University, 2008)
This research explores the relationship between poverty and the availability and use of an efficient public transport system. This is done by examining other third word cities, with particular reference to Bogotá (Colombia), which incorporated public transport in their transportation systems. The research concludes by pointing out lessons for Johannesburg that wants to implement a Bus Rapid Transit System and lower its poverty levels.
Keywords: Public transport; South Africa; Rapid transit system; Johannesburg